2001
DOI: 10.1046/j.1365-2648.2001.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perceptions of research: usefulness, implementation and training

Abstract: Overall, the present study suggests that educational and organizational improvements need to be introduced to transform nursing into a research-active profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 27 publications
0
23
0
6
Order By: Relevance
“…Dünyada ve ülkemizde lisans düzeyindeki hemşirenin araştırma sürecinde aktif rol almaktan ziyade araştırmacılara yardımcı olma rolünü üstlenmesi ve esas olarak araştırmanın etkili bir tüketicisi olması ve araştırma bulgularını uygulamaya aktarması beklenebilir. Pek çok ülkede hemşirelik öğrencilerinin araştırma farkındalığı ve tutumlarını inceleyen araştırmalar yapılmıştır [8][9][10] . Ülkemizde de hemşirelerin ve hemşire öğrencilerin araştırma konusundaki görüş ve tutumlarına ilişkin çalışmalar her geçen gün artmaktadır 11 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Dünyada ve ülkemizde lisans düzeyindeki hemşirenin araştırma sürecinde aktif rol almaktan ziyade araştırmacılara yardımcı olma rolünü üstlenmesi ve esas olarak araştırmanın etkili bir tüketicisi olması ve araştırma bulgularını uygulamaya aktarması beklenebilir. Pek çok ülkede hemşirelik öğrencilerinin araştırma farkındalığı ve tutumlarını inceleyen araştırmalar yapılmıştır [8][9][10] . Ülkemizde de hemşirelerin ve hemşire öğrencilerin araştırma konusundaki görüş ve tutumlarına ilişkin çalışmalar her geçen gün artmaktadır 11 .…”
Section: Introductionunclassified
“…Bu araştırma, farklı okullarda eğitim gören hemşirelik öğrencilerinin araştırmaya, gelişmelere farkındalığı ve tutumunun belirlenmesi amacı ile yapılmıştır. 7,9,12 . Soru formunun ön uygulaması, her okulda üçüncü sınıfta okuyan her biri 10 olmak üzere toplam 30 hemşirelik öğrencisi üzerinde yapılmıştır.…”
Section: Introductionunclassified
“…Several students had interesting ideas for future research, but had little motivation to follow through with them. Students emphasized this lack of motivation emanated from not expecting to study research, and having a poor understanding of the nature and usefulness of nursing research [5] . However, more positive perceptions of research were evident in the findings of a study carried out by Bjorkstrom, Johnasson, Hamrin, and Athlin [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Kennel, Burns, and Horn [4] noted that anecdotally, nursing students regard engaging in research projects as unrealistic given their other responsibilities within educational programs and view research projects as intimidating. In a qualitative study examining nursing students' perceptions of research, Ax and Kincade [5] found that students were uncertain about the usefulness of research in practice. Uncertainty was often linked to a lack of understanding of the research process or struggling to recall research terminology and skills.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students felt that they did not understand the meaning of the research education, especially in their primary courses [13,14] . Instead of education related to research, they wished to have more practical training [15] .…”
mentioning
confidence: 99%